ChemInform Abstract: Synthesis of Neplanocin A and Its 3′‐Epimer via an Intramolecular Baylis—Hillman Reaction. Issue 10 (March 2015) - Tan, Yun Xuan; Santhanakrishnan, Sridhar; Yang, Hai Yan; Chai, Christina L. L.; Tam, Eric Kwok Wai
Abstract The ester (I), readily available from D‐ribose, is transformed under optimized conditions to the stereodefined cyclopentene intermediate (II).